Developing statistical limits for using the light weight deflectometer in pavement construction quality assurance. Issue 4 (19th May 2018) - Volovski, Matthew; Labi, Samuel; Sommer, Kurt; Noureldin, Samy; Walker, Ron
Abstract : Traditional methods of evaluating the quality of pavement subbase and subgrade compaction require considerable time and resources. Therefore, agencies continue to seek and evaluate safe, reliable, rapid, and cost-effective alternatives for quality assurance of the field compaction of unbound pavement layers. The light weight deflectometer (LWD) is a promising alternative that is increasingly gaining attention. This study investigated the feasibility of developing statistical limits for the compaction of specified combinations of subbase and subgrade materials in terms of their LWD maximum allowable deflections (MAD), to replace the need for site-specific LWD limits derived from the onsite test sections. Statistical limits were developed for six common subgrade and subgrade–subbase combinations used for highway pavement construction: lime-modified, cement-modified, and natural subgrade and the first six-inch lift of Number 53 crushed stone subbase overlaying these subgrades. Two sources of data, test sections and acceptance tests, were used. For a given material type, the data from the former exhibited less variability between projects. The test section data yielded MADs that did not vary significantly between projects for cement- and lime-modified subgrade, non-modified subgrade, and six inches of Nr.53 crushed stone over lime-modified subgrade.